Flexion Teardrop Fracture of the Cervical Spine: Radiographic Characteristics - Kim, Kwang S.; Chen, Harry H.; Russell, Eric J.; Rogers, Lee F. (American Journal of Neuroradiology, 1988)
Teardrop fracture of the cervical spine is a confusing and loosely used term, often referring to any fracture with a triangular fragment in the involved body. The flexion teardrop fracture is a specific entity that should not be confused with other types of injury with a teardrop fragment. In a radiographic analysis of 45 patients with flexion teardrop fracture, the most characteristic feature was posterior displacement of the upper column of the divided cervical spine, observed in 78% of the cases. Other radiographic characteristics included backward displacement of the posterior fragment of the involved body, widening of the interlaminar and interspinous spaces, widening of the facet joint with backward displacement of the inferior facet, and kyphotic deformity of the cervical spine at the level of injury. The injury was frequently associated with sagittal-body and laminar fractures and occurred predominantly at the C5 level.